Diversity of gastropods (Mollusca: Gastropoda) in different altitude regions of the Zarafshan Mountains and adjacent areas, Uzbekistan - ULUGBEK URALOV; JASUR KUDRATOV; ABDUVAEIT PAZILOV; ZUVAIDULLO IZZATULLAEV; FAZLITDIN KHALIMOV; BEKZOD OTAKULOV; ABDURASHID JABBAROV; SEMYON FUNDUKCHIEV; YOQUTOY ORZIYEVA; GOLIB SUYUNOV; BAKHTIYOR MELIEV ABDUXAMIDOVICH; KHUSNIDDIN BOYMURODOV; DOSTON GULBOEV; XULKAR URINOVA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Uralov U, Kudratov J, Pazilov A, Izzatullaev Z, Khalimov F, Otakulov B, Jabbarov A, Fundukchiev S, Orziyeva Y, Suyunov G, Abduxamidovich BM, Boymurodov K, Gulboev D, Urinova X. 2025. Diversity of gastropods (Mollusca: Gastropoda) in different altitude regions of the Zarafshan Mountains and adjacent areas, Uzbekistan. Biodiversitas 26: 5012-5022. As an important part of the food chain in nature, it is of great importance to determine the systematic structure and diversity of mollusks. This study presents data obtained by assessing the current state of the taxonomic structure of gastropod mollusks in biogeographical regions with different vertical heights in the study area. The study area includes 15 locations in the Zarafshan Mountains of Uzbekistan and adjacent areas. The study sites were formed based on more than 3,000 samples collected in 2018-2025. It was found that the gastropod fauna of the region consists of 80 species belonging to 21 families and 35 genera. Using modern morphological and anatomical methods of species identification, Archaica haziratishaxika was identified for science; the following species were recorded for the first time as new species for the region, adding to the region's biodiversity: Sogdamnicola shadini, Lymnaea fragilis, Galba truncatula, Radix bactriana, Candaharia rozeni, Macrochlamys turanica, Macrochlamys kasnakowi, Vertigo antivertigo, and Chondrina intumescens. The results obtained will serve as a primary source for supplementing the data on the gastropod fauna of mountain ranges in Uzbekistan with the missing data on the Zarafshan Mountains and adjacent areas, and will provide specialists with the first information on this area.